(untitled) (Research, Society and Development, 2021)
A systematic review was performed to assess the reduction of intracanal microorganisms in teeth with pulp necrosis using photodynamic therapy (PDT) compared to calcium hydroxide (CH). The research sought randomized clinical trials that used PDT to assist in intracanal disinfection in teeth with pulp necrosis compared with the use of CH. The search was performed in PubMed, Scopus, Web of Science, LILACS, BBO, Cochrane Library and gray literature. IADR abstracts, records of unpublished essays, dissertations and theses were also searched. The Cochrane Collaboration Risk of Bias Analysis Tool was applied to assess the quality of the studies. 121 articles were identified. Only 5 studies remained in the qualitative synthesis, with one being considered to have “low” risk of bias and 4 considered to have an “undefined” risk of bias in the key domains. The 5 articles were included in the meta-analysis. The reduction of microorganisms in teeth with pulp necrosis comparing PDT to CH was 0.01 (confidence interval [CI] = -0.04 to 0.07, p = 0.59). This result demonstrates that there was no difference between the therapies. It can be concluded that there was no difference between the use of PDT or CH in the intracanal disinfection of teeth with pulp necrosis.